In Vitro Impact of Triatomine Salivary Glands Extracts Introduced to Endothelial Cells - Abernathy, Roger; Montenegro-Cadena, Lidia; Londono-Renteria, Berline (My University, 2018)
Chagas Disease (AKA Trypanosomiasis) is caused by biting/feeding behavior from the arthropod vector Triatoma (subfamily of Reduviidae family), that house the endoparasite Trypanosoma cruzi, which can then be passed to human and mammalian hosts (Schmidt, et al., 2011). Resources are currently being utilized to help minimize the effects and susceptibility of Chagas within endemic areas. Previous research has demonstrated that there are biochemical interactions between specific Triatoma salivary proteins and host cells (Ribeiro, Assumpção, Van Pham, Francischetti, & Reisenman, 2012).This study examined the interactions made from salivary proteins procured from the T. sanguisuga and T. indictiva species with the expression of two glycoproteins, fibronectin (angiogenic) and thrombospondin (antiangiogenic) when exposed to Human Umbilical Vein Endothelial Cells (HUVECs).
Keywords: Fall 2018